Contraction and release - Beausoleil EJ (ARCHÉE)
With this issue and the next two we will follow the experience Into the Midst , workshop and led by SenseLab under the direction of Erin Manning and Brian Massumi . In texts of reflection or contemporaneous notes Eleven participants will recount their experiences in the project, which lasted several months and resulted in the multisensory event This is not a show. The dome in the middle | Immersion ≈ Emergence to Satosphère of Montreal. In this first part Erin Manning, Louise Boisclair, Ana Ramos and Emily Beausoleil give the premises.